PERFORMANCE ANALYSIS OF KEDUNGHALANG AND YASMIN INTERSECTION DUE TO THE CONSTRUCTION OF BOGOR RING ROAD TOLL - MUSTAQIM (NIM : 15007145); Pembimbing : Prof. Dr. Ir. Ofyar Z. Tamin, M.Sc., Ph.D.,
Intersection is a public road that is part of road network system and a knot of streets segment that converge or intersect. Intersection consists of several components, one of which is the approach of intersection. The approach of intersection is the area of arms intersection of the road for vehicles to queue before exiting past the stop line. Intersection performance influenced the performance of its components, including the intersection approach. Performance analysis is needed to determine the performance and problems that exist in the intersection approach which will also be known to the intersection as a whole. This study examines the intersection performance based on queue length and the value of delay, as well as checking the geometric and time of service. The intersection that studied here is signalized intersections. The used of data in this study are primary and secondary data. Primary data obtained from the results of field surveys while the secondary data obtained from the relevant institution. The calculation of the signalized intersection using MKJI 1997. The Conclusion of this study showed that one of the intersections performance was not good so it is necessary to improve which is composed of cycle time optimization, phase changes, geometric changes, and making the overpass.